Bulas de medicamentos comercializados no Brasil enquanto fontes de informação: em foco a qualidade da informação nelas contidas após a resolução RDC nº 47/2009 da Anvisa - Juliana Moreira Pinto (2013)
This research aimed to evaluate the quality of information of labels for patients, marketed in Brazil, after the ANVISA RDC 47/2009, based on the intrinsic attributes of information quality described in the literature of information science, and are also used as criteria to evaluate the quality of information in the area of Health. As methodological procedures, we used a qualitative approach, performed in two stages: a) analysis of the informational content of labels for patients and b) analysis of the responses of patients to a health center of Belo Horizonte and the UniãoAuxiliadora dos Cegos de Minas Gerais, structured interviews on the labels of medicines as a source of information. We conclude that the intrinsic attributes of information quality are observed during the preparation of labels, but believes that adjustments still need to be made in terms of accuracy and completeness, as compared with the information contained in the Dicionário Terapêutico Guanabara and database Micromedex, some labels submitted incomplete or divergent from those described in the literature. The label also does not provide guidance on the disposal of unused medications, accrued or leftovers, seen as fundamental to the preservation of the environment and safety "popular" against accidental ingestion of substances that may lead to the emergence of serious adverse reactions, poisoning and other issues that may compromise the health and quality of life of users. Among patients who reported reading the label it was found that some agreed that this is an important source of information about medicines, others highlighted the fact that it provide information about side effects and contraindications that lead patients to have fear of ingesting the drug or even give up treatment.